Pelatihan Pipe Welder Kepada Karyawan PT. Perintis Makmur Indonesia Dengan Metode Pengelasan Shielded Metal Arc Welding - Wirakusuma, Kadex Widhy; Kadriadi, Kadriadi; Siswanto, Yudi; Amiruddin, Amiruddin; Alfian, Muhammad; Fathurrasuli, Fathurrasuli (Politeknik ATI Padang, 2024)
PT. Perintis Makmur Indonesia (PMKI) is a smelting company that plays an important role in workforce absorption in the Morowali area. In particular, the mechanical department, consisting of 18 employees, requires an upgrade in pipe welding skills using the SMAW welding method. This is due to the fact that the mechanics are currently only capable of performing plate-to-plate welding, whereas they are required to have pipe-to-pipe welding skills to support their work. To enhance its employees' competencies, particularly in pipe welding, PT PMKI collaborated with the Morowali Metal Industry Polytechnic to organize a Shielded Metal Arc Welding (SMAW) training program for its employees. The primary goal of this training was to improve the employees' skills in performing pipe welding safely and efficiently. The training methods included lectures, discussions, and hands-on practice in the workshop, along with evaluations through pre-tests and post-tests. A total of 18 mechanics participated in this five-day training. The materials covered welding safety, SMAW techniques, and defect handling in welding. The results showed a significant increase in participants' understanding and skills. The initial understanding level, as measured by the pre-test, was only 19.8%. After the training, participants' understanding increased to 93.2%, as indicated by the post-test results. This training successfully improved the employees' pipe welding competencies, which are crucial for supporting the company’s operations.